2007
DOI: 10.1063/1.2756830
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast studies of gold, nickel, and palladium nanorods

Abstract: Steady state and ultrafast transient absorption studies have been carried out for gold, nickel, and palladium high aspect ratio nanorods. For each metal, nanorods were fabricated by electrochemical deposition into approximately 6 microm thick polycarbonate templates. Two nominal pore diameters(10 and 30 nm, resulting in nanorod diameters of about 40 and 60 nm, respectively) were used, yielding nanorods with high aspect ratios (>25). Static spectra of nanorods of all three metals reveal both a longitudinal surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 98 publications
3
47
0
Order By: Relevance
“…The average damping time for the silver nanowires was (78.4 AE 22.3) ps, and the average quality factor was determined to be Q Ag;wire ¼ (23.2 AE 6.1) (errors equal standard deviations). The damping times measured in our experiments are much longer than those from ensemble measurements for the breathing mode of nanowires, [51,52] as expected from the broad distribution of widths in these samples.…”
Section: Silver Nanowiresmentioning
confidence: 72%
“…The average damping time for the silver nanowires was (78.4 AE 22.3) ps, and the average quality factor was determined to be Q Ag;wire ¼ (23.2 AE 6.1) (errors equal standard deviations). The damping times measured in our experiments are much longer than those from ensemble measurements for the breathing mode of nanowires, [51,52] as expected from the broad distribution of widths in these samples.…”
Section: Silver Nanowiresmentioning
confidence: 72%
“…Significant research efforts have been focused on the study of acoustic phonon modes in metallic nanoparticles using both ensemble [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] and single-particle 23,[27][28][29][30][31][32][33][34][35][36] transient extinction measurements. These studies have shown that the elastic constants of the nanoparticles, obtained from the measured lattice vibrations, agree well with those of the corresponding bulk materials, suggesting that, generally speaking, there is no change in the elastic properties of nanoscale objects because of their smaller size 40 .…”
mentioning
confidence: 99%
“…The other research group also reported the TAS studies on Au NRs at 410 nm excitation wavelength and observed that the transient bleaching of TSPR and LSPR absorptions show similar intensity results to previous studies. 911,1720…”
Section: Resultsmentioning
confidence: 99%
“…The few experimental studies have been focused on the electron dynamics of the Au NRs by pump–probe transient absorption spectroscopy. 911,1720…”
Section: Introductionmentioning
confidence: 99%